Pelaksanaan Evaluasi Hasil Belajar Siswa Dalam Pendidikan Jasmani Olahraga Dan Kesehatan Di Smp Negeri Se Kecamatan Jepara Tahun 2021 (Indonesian Journal for Physical Education and Sport, 2021)
The purpose of the study was to find out how the evaluation of student learning outcomes at state junior high schools throughout the district of Jepara was carried out. The method used is a survey with data collection techniques using a questionnaire in the form of a questionnaire. The subjects in this study were teachers of Physical Education, Sports and Health at State Junior High Schools throughout the District of Jepara, namely 16 teachers. The data analysis technique used quantitative descriptive analysis as outlined in the form of percentages. The results showed that the Implementation of Evaluation of Student Learning Outcomes in Physical Education, Sports and Health in Public Junior High Schools throughout the Jepara District in 2021 was in the "Very Poor" category of 0% or 0 teachers, in the "Less" category of 25% or 4 teachers, in the "Enough" category of 43.75% or 7 teachers, in the "Good" category of 25% or 4 teachers, and in the "Very Good" category of 6.25% or 1 teacher. The conclusion of this study is that the implementation of the evaluation of student learning outcomes in physical education in sports and health in public junior high schools throughout the Jepara sub-district in 2021 reached a sufficient category of 43.75%.